A Residual Method Using Bézier Curves for Singular Nonlinear Equations of Lane-Emden Type - Adiyaman, Meltem; Oger, Volkan (Kuwait Journal of Science, 2017)
In this article, we introduce a new method to solve a singular non-linear equation of the Lane-Emden type by approximating the solution with Bernstein polynomials. This method is based on the minimization of a residual function using Taylor’s series expansion. We also apply this method to problems that are solved by other methods and the obtained results show that our method is efficient, applicable and has great potential than others.